2015
DOI: 10.1002/ente.201500188
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Low‐Fracture Conductivity in Soft Shale Formations: An Experimental Study

Abstract: Sufficient fracture conductivity must be sustained in fracture networks created by massive slickwater fracturing to continue the exploitation of ultralow‐permeability shale formations. However, unrealistic conductivity values obtained under ideal laboratory conditions are generally utilized for fracture designs. In this study, we outlined an experimental program to measure the conductivity of different possible fracture patterns in the fracture network, such as standard smooth fractures and shear fractures, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…(2014) created X-ray microtomographic images from shear induced fractures and the roughness values obtained varied from 1.8 to 1.95 mm along the length of the rock samples. Zou et al (2015) conducted experiments on 20 fractured shale samples and found the average asperity height to be 1.88 mm. An experimental study (Zhang et al 2014) on Barnett Shale samples reveals that the surface topography of the displaced fracture can be altered because of rock failure, and the fracture surface exhibited parallel strips of crushed asperities.…”
Section: The Cause Of Variable Fracture Compliancementioning
confidence: 99%
“…(2014) created X-ray microtomographic images from shear induced fractures and the roughness values obtained varied from 1.8 to 1.95 mm along the length of the rock samples. Zou et al (2015) conducted experiments on 20 fractured shale samples and found the average asperity height to be 1.88 mm. An experimental study (Zhang et al 2014) on Barnett Shale samples reveals that the surface topography of the displaced fracture can be altered because of rock failure, and the fracture surface exhibited parallel strips of crushed asperities.…”
Section: The Cause Of Variable Fracture Compliancementioning
confidence: 99%
“…In the field condition, there are many factors that should be taken into consideration for particle flow simulation. The collisions between particles, the non-uniform sizes and densities of mixed particles, and the different amounts of every kind of particle all would affect the distribution of deposited particles in fractures (Huang et al, 2018;Zou et al, 2015). In relevant work, DEM was proposed as a suitable method to fully consider these factors (Wu et al, 2017;Zeng et al, 2016Zeng et al, , 2018Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that particle size, mass loading, and the roughness degree play roles on the particle velocity profiles (Sommerfeld and Kussin, 2004). The uneven distribution of particles in the rough fracture was studied in experiments as well (Huang et al, 2018;Tan et al, 2017;Zou et al, 2015). On the other hand, various numerical simulation works obtained more detailed information on particle deposition characteristics, such as the effects of the micro shape of the rough channel (Dorari et al, 2015;Hemmati and Rafee, 2018;Hong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the production from the low-permeability reservoirs, it is necessary to increase their permeability through fracturing such as hydraulic fracturing. Usually, a fracturing fluid is injected under high pressure to hydraulically crack the reservoir rock in order to create fractures [2][3][4][5]. However, oil-based fracturing fluids used for hydraulic fracturing often bring about environment and safety concerns.…”
Section: Introduction: As a Well-established Stimulation Technique Formentioning
confidence: 99%
“…Bishop et al [7] reported that guar gum can be cross-linked with borates by way of its 3,4-cis-hydroxyl radical in the galactose side chains, leading to the formation of a three-dimensional network responsible for the gelation. Kramer et al [8] found that the cross-linking of guar gum with borate is based on the hydrolysis of B(OH) 4 − anion. Namely, B-OH can form hydrogen bonds with the cis-hydroxyl radical of the polysaccharide, thereby connecting two strains of guar gum, as illustrated in Fig.…”
Section: Introduction: As a Well-established Stimulation Technique Formentioning
confidence: 99%